Quality Mapping of Remote Elementary School-Based on e-EDS - Piter Joko Nugroho; Theo Jhoni Hartanto; Slamet Winaryo (Universitas Negeri Malang, 2021)
This study aims to map the quality of elementary schools in remote areas in Kapuas and North Barito districts Central Kalimantan Province based on modified e-EDS by considering the ease of use and understanding of the "user" (principal of remote primary schools). This descriptive study using a qualitative approach was conducted in 9 (nine) remote elementary schools in the Kapuas and North Barito districts. Sources of data in this study consisted of nine school principals and the education officials from the two districts. Data collection techniques were carried out by interview (interview), observation, and e-EDS instruments which were developed referring to the SNP for elementary and secondary education. Data analysis using interactive data analysis. The data validation technique used the confirmability technique. The results showed that all elementary schools in remote areas received "red report cards". The issue of disparities in the quality of education in remote areas has not been properly handled by district and provincial policymakers and related stakeholders. In this article, we provide recommendations for conducting policy lending from countries that are successful in overcoming education problems in remote areas as a means of conducting policy lessons to address the quality problems of remote elementary schools in the future.